Pentingnya Pembinaan Iman Bagi Calon Keluarga Muda Katolik - Philipus Willy Adi Nugroho; Intansakti Pius X (Jurnal Magistra, 2023)
Originating from the word "Katekese," this term is derived from the Greek language, namely "Katecho." When translated into Indonesian, it consists of "Kat," meaning downward/square/wide, and "Echo," which signifies proclaiming/teaching. Consequently, "katekese" in Indonesian means religious teaching or education, particularly for baptismal candidates, explaining catechism lessons to children, and the general public. In this context, katekese will be discussed in more detail, specifically focusing on "Family Catechesis," which forms the foundation of human faith.